Why should the carbon tax be floating? A Tobin’s Q model applied to green investment - Nicolas Piluso (Environmental Economics, 2023)
The carbon market reform is controversial because the modalities of carbon pricing foreseen risk reducing the performance of companies and negatively affecting the economy. The objective of this paper is to show that the carbon tax can be floating and adapt to the economic situation while maintaining its ecological efficiency. Herein, Tobin’s Q model, which has become a standard in the literature for explaining the investment decision, is applied to the green investment decision. A carbon tax is introduced into the firm’s maximization program to see how carbon pricing changes the outcome of the traditional model. The model shows that green investment depends on the sum of the stock price and the carbon price, which suggests the possibility of modulating this amount according to the upward or downward trend of the stock price to avoid permanently penalizing the competitiveness of firms. The study also demonstrates how the financial market is likely to value green investments and that such investments will likely generate shareholder value through several channels. Indeed, green investments impact the firm’s turnover and the minimum income required by the shareholder. Such a modulation of the carbon tax according to the economic cycle would make reconciling ecological and economic efficiency possible.